Likely Effect of Gender and Education on Information Adoption and Utilization among Sugarcane Farmers in the Nyanza Region, Kenya - Ochieng, Ben Jack Otieno; Nyongesa, Destaings Nyenyi; Odhiambo, Scholastica Achieng (Journal of Social Economics Research, 2020)
A lack of education and training is what limits the adoption of technology and, hence, development by small scale farmers. Controversy reigns on whether women are less or more likely to adopt and utilize agricultural information. Similarly, there is no agreement on whether education exacerbates the adoption of agricultural information. Given this lack of clarity, this study aimed to determine the likelihood of the effect of gender and the level of education on the adoption and utilization of information gadgets among sugarcane farmers in the Nyanza region, Kenya. This study adopted technology diffusion theory and correlational research design. Stratified, random sampling was purposively used among 317 sugarcane farmers. Chi-square and multinomial logistic regression were used to generate results which showed that women were significantly less likely to use radios than men. However, the females were more likely to utilize agricultural information in planting, finding new markets, sourcing for raw materials, seeking for referrals, checking for weather updates and farm inputs than men. Regarding the levels of education, those with a primary education were significantly less likely to utilize information gadgets to discover information than those with a secondary education.